2018
DOI: 10.1080/07357907.2018.1445262
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type Isocitrate Dehydrogenase 1 Over-Expression is Related to Cancer Stem Cells Survival in Lung Adenocarcinoma

Abstract: Altered metabolism is one of the characteristics of cancer cells. We evaluated the expression of wild-type Isocitrate Dehydrogenase 1 (IDH1) and the cancer stem cells (CSCs) marker CD44 by real-time PCR and levels of reduced form of glutathione in lung biopsies of 32 adenocarcinoma patients and 18 control subjects. We found that IDH1 and CD44 expression and the levels of reduced form of glutathione were significantly higher in lung adenocarcinoma patients. IDH1 was positively correlated with CD44 and reduced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…On the other hand, IDH1 was found overexpressed in numerous cancers. Importantly, several studies indicate that IDH1 overexpression correlates with poor OS in the non-small cell lung carcinoma (NSCLC) patients adenocarcinoma and squamous cell carcinomas [62,63,64,65]. It has been demonstrated that shRNAs targeting IDH1 decreased in vitro and in vivo growth of NSCLC cell lines [62].…”
Section: Overexpression Of Wild-type Idh1 In Cancersmentioning
confidence: 99%
“…On the other hand, IDH1 was found overexpressed in numerous cancers. Importantly, several studies indicate that IDH1 overexpression correlates with poor OS in the non-small cell lung carcinoma (NSCLC) patients adenocarcinoma and squamous cell carcinomas [62,63,64,65]. It has been demonstrated that shRNAs targeting IDH1 decreased in vitro and in vivo growth of NSCLC cell lines [62].…”
Section: Overexpression Of Wild-type Idh1 In Cancersmentioning
confidence: 99%
“…Although wild-type IDH1 has had much less attention compared to the research on glioma with IDH1 mutation, several studies have revealed that wild-type IDH1 is overexpressed in several types of cancers, including non-small cell lung carcinoma (NSCLC) (17,18), pancreatic adenocarcinoma (PDAC) (19), and primary glioblastoma (20,21). Importantly, these studies show that IDH1 is overexpressed in over 60% of primary glioblastoma patients and is correlated with poor overall survival.…”
Section: Wild-type Idh1 Is Overexpressed In Many Primary Glioblastomamentioning
confidence: 99%
“…Indeed, a recent study by Su et al highlighted that IDH1 wt (not the mutated form IDH1 R132C ) promotes cell proliferation, invasion and migration in iCCA cell lines by regulation of αKG and NADPH levels [138]. These results are not surprising because over recent years it has emerged that an aberrant expression of non-mutated IDH1 in numerous cancers (e.g., non-small cell lung carcinoma, squamous cell lung cancer, pancreatic ductal adenocarcinoma, primary glioblastoma) [139][140][141][142] correlates with therapy resistance, an aggressive phenotype and poor prognosis [141,[143][144][145]. The biological consequences of IDH1 up-regulation are ascribable to the central role of this enzyme in the regulation of both metabolic and epigenetic processes.…”
Section: Future Perspectives Of Idh1 Inhibitors Use In Intrahepatic Cmentioning
confidence: 99%